Comparison of standing long jump technique performed by subjects from different age groups - Hraski, M.; Hraski, Ž; Prskalo, I. (Baltic Journal of Sport and Health Sciences, 2015)
Background: The aim of this study was to determine kinematic parameters relevant for the proficient performance of standing long jump (SLJ) test in boys and adolescents. Methods: The investigation was conducted on 120 participants divided into five experimental groups of 20 boys and adolescents aged 4-18 and one control group composed of 20 students from the second year of Faculty of Kinesiology whose performance was considered as a model of proficient execution of analysed test. The set of variables was composed of 15 kinematic parameters. For determining the influence of selected kinematic parameters on proficiency of standing long jump test, the Stepwise Regression Analyses was used. Results: The results showed the existence of specific relationship between selected kinematic parameters that significantly affected the execution of standing long jump test in each age group. Conclusion. It can be concluded that, according to analysed kinematic parameters, technique of standing long jump significantly differ from early age to maturity.